2021
DOI: 10.1002/advs.202103173
|View full text |Cite
|
Sign up to set email alerts
|

Highly‐Tunable Intrinsic Room‐Temperature Ferromagnetism in 2D van der Waals Semiconductor CrxGa1−xTe

Abstract: The combination of semiconductivity and tunable ferromagnetism is pivotal for electrical control of ferromagnetism and next-generation low-power spintronic devices. However, Curie temperatures (T C ) for most traditional intrinsic ferromagnetic semiconductors (≤200 K) and recently discovered two-dimensional (2D) ones (<70 K) are far below room temperature. 2D van der Waals (vdW) semiconductors with intrinsic room-temperature ferromagnetism remain elusive considering the unfavored 2D long-range ferromagnetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…34 This is also consistent with many previous reports on the introduction of ferromagnetism by Cr doping. 20,21 Corresponding to our previous XRD tests, the lower Curie temperature of 2# than that of 1# is attributed to the presence of more Cr content in a higher valence state.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…34 This is also consistent with many previous reports on the introduction of ferromagnetism by Cr doping. 20,21 Corresponding to our previous XRD tests, the lower Curie temperature of 2# than that of 1# is attributed to the presence of more Cr content in a higher valence state.…”
Section: Resultssupporting
confidence: 69%
“…14–18 The introduction of ferromagnetism in vdW crystals can also be achieved by the doping of magnetic elements such as Fe 1/3 TaS 2 , CrWoTe 2 , CrGaTe, and CrMoTe 2 . 19–22…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, Ferromagnetic van der Waals crystals near room temperature were obtained by Cr doping in WTe 2 , 158 2H-MoTe 2 , 159 VTe 2 160 and GaTe. 161 It is an effective route to regulate the Curie temperature of 2D ferromagnetic crystals through ionic gates. The original Curie temperature of a monolayer Fe 3 GeTe 2 was 205 K, but an ionic gate can raise its T C to over room temperature (Fig.…”
Section: Magnetic Transition Temperature and Magnetic Regulationmentioning
confidence: 99%
“…As a crucial component of the 2D material family, due to the promising application prospect in spintronics and magnetic memory devices, , 2D magnetic materials with exceptional electrical , and photoelectrical , properties as well as novel magnetic properties have received extensive attention. Particularly, it is found that monolayer Fe 3 GeTe 2 still retained ferromagnetic long-range order at low temperatures. Thus far, ultrathin Cr x Ga 1– x Te nanosheets have exhibited intrinsic room-temperature ferromagnetism, which renders them ideal candidates for carrier control . Despite 2D magnetic materials hold promising prospects for exploration and practical applications, its magnetic behavior especially in the magnetic domain structure is still in its nascent stages.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 Thus far, ultrathin Cr x Ga 1−x Te nanosheets have exhibited intrinsic room-temperature ferromagnetism, which renders them ideal candidates for carrier control. 13 Despite 2D magnetic materials hold promising prospects for exploration and practical applications, its magnetic behavior especially in the magnetic domain structure is still in its nascent stages. Consequently, it is essential to explore the controllable growth and the magnetic domain structure of 2D magnetic materials.…”
Section: Introductionmentioning
confidence: 99%